Coronavirus proteins: biogenesis of avian infectious bronchitis virus virion proteins. - Stern, D F (1982)
We examined the synthesis of viral structural proteins in cultured cells infected with the avian coronavirus infectious bronchitis virus. Tryptic peptide mapping was used to determine the structural relationships of the intracellular proteins to the virion polypeptides. Pulse-chase experiments were performed to identify precursors to the virus-specific proteins. We found that the nucleocapsid protein, P51, and the small viral membrane proteins GP31, GP28, and P23 do not undergo post-translational proteolytic processing. In contrast, GP90 and GP84, the two large virion membrane proteins, were found to be produced by cleavage of a single precursor, GP155. This demonstrated that at least one coronavirus mRNA specifies two virion proteins.